Modelos de negócios à luz da Teoria Neo-institucional: um estudo em health techs brasileiras - Fróes, Luiza Ten-Cate (Universidade do Vale do Rio dos Sinos, 2021)
The technological transformations arising from industry 4.0 enable advantages for innovations in products, services and business models, as well as boosting digital entrepreneurship. In this context, healthcare startups, such as healthcare technologies, come with technologies to improve or transform the patients' experience, and have the potential to revolutionize the current fragile health system. However, health techs need to consider institutional factors in the health sector, which is highly regulated, and which can act both as an opportunity and as a barrier to the creation of innovative business models. In order to address this issue, this study aims at exploring the influence of institutional factors in the creation and application of business models of Brazilian health techs, under the lens of the Neo-institutional Theory. For the development of the research, a multiple case study was carried out among 12 Brazilian health techs, located in different regions of the country. The data indicate that in the stage of creating the business model, there is a higher incidence of the culturalcognitive pillar and entrepreneurs present a more centered view on their personal objectives and purposes of the new business. In the stage of applying the business model, factors related to the normative pillar and the regulatory pillar had more incidence, since entrepreneurs get a broader view of the barriers and opportunities in the institutional context of health. It was also highlighted in the application stage the search for legitimacy, with the actions that aim at making the business model seen as worthy and acceptable in the institutional context. In short, it is possible to conclude that institutional factors affect the stages of creation and application of the health techs business model in a different way. This study contributes to the literature on business models and digital entrepreneurship, highlighting the importance of analyzing institutional factors in business modeling.
Keywords: Empreendedorismo digital; Modelo de negócio; Health techs; Teoria Neo-institucional; Digital entrepreneurship; Business model; Neo-institutional Theory; ACCNPQ::Ciências Sociais Aplicadas::Administração